2004
DOI: 10.1111/j.0021-8901.2004.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating grazing damage by white‐fronted geese: an optimal foraging approach

Abstract: 1.Agricultural damage by wildlife is a serious constraint on the coexistence of humans and wildlife. Understanding the behavioural processes involved in such agricultural damage will inform management actions. In this study, a linear programming model based on optimal foraging theory was used to formulate management strategies designed to reduce wheat damage caused by white-fronted geese Anser albifrons around Lake Miyajimanuma in Japan. 2. Geese feed on rice grains or wheat leaves. Their choice of food is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 61 publications
2
40
0
2
Order By: Relevance
“…Food quality did not seem to affect goose distribution. Indeed, the sites selected by geese were of sufficiently high forage quality (nitrogen concentrations from 2.6% to 5.5%), which was well beyond the limit for Barnacle Geese of 2.4% (Prop & Deerenberg 1991, Amano et al 2004). This lack of food quality effect is different from previous field experimental studies (Bos et al 2005, van der Graaf et al 2007, which demonstrated that fertilized plots were preferred above control plots.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Food quality did not seem to affect goose distribution. Indeed, the sites selected by geese were of sufficiently high forage quality (nitrogen concentrations from 2.6% to 5.5%), which was well beyond the limit for Barnacle Geese of 2.4% (Prop & Deerenberg 1991, Amano et al 2004). This lack of food quality effect is different from previous field experimental studies (Bos et al 2005, van der Graaf et al 2007, which demonstrated that fertilized plots were preferred above control plots.…”
Section: Discussionmentioning
confidence: 93%
“…Small herbivores require a higher nutrient concentration in their diets than large herbivores, as they are less capable of utilizing poor quality plants (Prins & Ydenberg 1985, Durant et al 2004, Prins & van Langevelde 2008. For instance, the Barnacle Goose Branta leucopsis requires food containing more than 15% crude protein to meet nitrogen requirements (Prop & Deerenberg 1991, Amano et al 2004. Furthermore, waterfowl have food retention times as short as a few hours (Prop & Vulink 1992, McKay et al 1994, which is reflected by a high throughput and defecation rate (Owen 1980).…”
mentioning
confidence: 99%
“…Hence, when faced with the choice between prey species (all other things being equal), consumers should select the one that will deliver highest energy intake and therefore maximum fitness (Charnov 1976). Although initially thought to be of trivial importance (Pyke, Pulliam & Charnov 1977), recent empirical studies have shown that factors such as nutrient content (McKay, Bishop & Ennis 1994; Hassall, Riddington & Helden 2001), digestibility (Prop & Vulink 1992), or a combination of these factors (Amano et al . 2004; Durant, Fritz & Duncan 2004) may substantially affect resource selection.…”
Section: Introductionmentioning
confidence: 99%
“…However, the quality of rice fields as spring habitat for pintails likely depends on how rice is harvested and postharvest treatment of stubble (Shimada 1999, Kross et al 2008). Also, availability of waste rice diminishes with time since harvest (Amano et al 2004, Manley et al 2004). Because spring staging occurred ∼5 mo after most rice had been harvested in Japan, invertebrates and seeds of other moist soil plants in rice fields were likely used by migrating pintails (Stafford et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Because spring staging occurred ∼5 mo after most rice had been harvested in Japan, invertebrates and seeds of other moist soil plants in rice fields were likely used by migrating pintails (Stafford et al 2010). Furthermore, feeding by migrating White‐fronted Geese on the core stopover area in Hokkaido reduced the amount of waste rice available to pintails in spring (Amano et al 2004), likely increasing the importance of other food items.…”
Section: Discussionmentioning
confidence: 99%